Automatic Processing of the Semantic Level through Ontology Construction (A Case Study of Motion and Stasis Verbs) - Hadjebar, Radia (LANGUAGE ART, 2024)
Computational linguistics focuses on formalizing language characteristics and rules for computer processing. While Arabic has successfully employed artificial intelligence in computational phonology, morphology, and syntax, semantic-level processing remains challenging. The core issues involve enabling computers to: (1) understand natural language with human-like comprehension, and (2) distinguish between literal and metaphorical word meanings to reduce the semantic ambiguity plaguing Arabic in digital environments. This study proposes an ontology-based methodology for Arabic semantic processing. Focusing on the semantic field of motion and stasis verbs, we extracted verb meanings from the "Ma'ajim Al-Ma'ani" dictionary and analyzed their interrelations. The resulting semantic network formally represents relationships between these verbs. Using the Web Ontology Language (OWL) - which enables systematic organization, classification, and linking of meanings - we developed an ontology that facilitates both human and machine interpretation.